Law in literature: surrealist images in Francisco (Paco) Espínola’s «María del Carmen» - Garcé, Luis Meliante (2024)
The link between literature and law has hardly been explored in Uruguay, let alone its connection with surrealism. Although this relationship appears initially distant, there are works that allow an analysis from this perspective. This paper studies the short story ‘María del Carmen’ by Francisco Espínola and aims to broaden the space for reflection on the potential of the relationship between law and literature and, in particular, with surrealism as an avant-garde aesthetic expression. Based on this objective, the following legal themes will be studied: gender, justice by one’s own hand, consent in marriage and its surrealist resolutions, in short, the absence of law and the conflict between principles. In other words, the question will be answered: is it possible to call for reflection on legal phenomena from a surrealist literary point of view?